Blue potatoes, orange tomatoes - Creasy, Rosalind; Heller, Ruth, 1924- (San Francisco : Sierra Club Books for Children, 1997)
Describes how to plant, grow, and cook a variety of unusually colored vegetables, including red corn, yellow watermelons, and multicolored radishes.
"A Sierra Club book"--Cover.
Includes index.
Book Links (A.L.A.)
School Library Journal
Wilson's Children
Appraisal-Science Books for Young People, February 2009
Keywords: Cooking (Vegetables) -- Juvenile literature; Vegetable gardening -- Juvenile literature; Vegetables -- Varieties -- Juvenile literature; Cooking (Vegetables); Gardening; Vegetable gardening; Vegetables; Cooking -- Vegetables; Vegetable gardening; Vegetables